Decision-Making Under Ambiguity or Risk in Individuals With Alzheimer’s Disease and Mild Cognitive Impairment - Sun, Tingting; Xie, Teng; Wang, Jing; Zhang, Long; Tian, Yanghua; Wang, Kai; Yu, Xin; Wang, Huali (Frontiers in Psychiatry, 2020)
Background: Making advantageous decisions is essential in everyday life. Our objective was to assess how patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) make decisions under conditions of ambiguity or risk. In addition, the study also aimed to examine the relationship between decision-making competence and memory and executive function. Methods: Patients with MCI (n = 36) and AD (n = 29) and healthy elderly controls (HC, n = 34) were recruited from the memory clinic. All subjects were administered a comprehensive neuropsychological battery test. We used the Iowa Gambling Task (IGT) to measure decision-making under ambiguity and the Game of Dice Task (GDT) to measure decision-making under risk. Pearson’s correlation was used to examine the relationship between the performance of IGT and GDT with delayed recall and the Stroop test. Results: In the GDT, the proportion of those making advantageous choices was lower in the AD group than in the HC group (p = 0.01), but the MCI and HC groups did not differ (p = 0.14). With regard to the ratio of accepting negative feedback, the AD (p < 0.01) patients were significantly different from the HC patients, and the MCI (p = 0.06) and HC groups did not differ. The IGT, MCI and AD patients selected randomly from advantageous and disadvantageous decks (p = 0.94 and p = 0.54) showed no significant change in performance over time. In contrast, the HC group made increasingly frequent advantageous selections over time (p = 0.04). Furthermore, the proportion of advantageous decision-makers for the GDT had a linear relationship with delayed recall of the Hopkins Verbal Learning Test and Stroop color words (p < 0.01 and p < 0.01, respectively). Conclusion: Our findings suggest that MCI and mild AD may compromise decision-making ability under ambiguity but not decision-making under risk. Reduced decision-making performance is closely correlated with lower executive functions and memory.